Receptor-independent transfer of low density lipoprotein cargo to biomembranes - Axmann, M; Sezgin, E; Karner, A; Novacek, J; Brodesser, MD; Röhrl, C; Preiner, J; Stangl, H; Plochberger, B (American Chemical Society, 2019)
The fundamental task of lipoprotein particles is extracellular transport of cholesterol, lipids, and fatty acids. Besides, cholesterol-rich apoB-containing lipoprotein particles (i.e., low density lipoprotein LDL) are key players in progression of atherosclerotic cardiovascular disease and are associated with familial hypercholesterolemia (FH). So far, lipoprotein particle binding to the cell membrane and subsequent cargo transfer is directly linked to the lipoprotein receptors on the target cell surface. However, our observations showed that lipoprotein particle cargo transport takes place even in the absence of the receptor. This finding suggests that an alternative mechanism for lipoprotein-particle/membrane interaction, besides the receptor-mediated one, exists. Here, we combined several complementary biophysical techniques to obtain a comprehensive view on the nonreceptor mediated LDL-particle/membrane. We applied a combination of atomic force and single-molecule-sensitive fluorescence microscopy (AFM and SMFM) to investigate the LDL particle interaction with membranes of increasing complexity. We observed direct transfer of fluorescently labeled amphiphilic lipid molecules from LDL particles into the pure lipid bilayer. We further confirmed cargo transfer by fluorescence cross-correlation spectroscopy (FCCS) and spectral imaging of environment-sensitive probes. Moreover, the integration of the LDL particle into the membranes was directly visualized by high-speed atomic force microscopy (HS-AFM) and cryo-electron microscopy (cryo-EM). Overall, our data show that lipoprotein particles are able to incorporate into lipid membranes upon contact to transfer their cargo in the absence of specific receptors.